HTN: a new hierarchical iterconnection network for massively parallel computers - Rahman, M.M. Hafizur; Susumu, Horiguchi (The Institute of Electronics, Information and Communication Engineers, Japan, 2003)
Interconnection networks usually suffer from Little's Law: low cost implies low performance and high performance is obtained high cost. However, hierarchical interconnection networks provide high performance at low cost by exploring the locality that exists in communication patterns of massively parallel computers. In this paper, we propose a new hierarchical interconnection network, called Hierarchical Torus Network (HTN). This network reduces the number of vertical links in 3D stacked implementation while maintaining good network features. This paper addresses the architectural details of the HTN, and explores aspects such as the network diameter, average distance, bisection width, peak number of vertical links, and VLSI layout area of the HTN as well as for several commonly used networks for parallel computers. It is shown that the HTN possesses several attractive features including small diameter, small average distance, small number of wires, a particularly small number of vertical links, and economic layout area.